Determinan Sinkronisasi Dokumen Anggaran Pendapatan dan Belanja Daerah (APBD) dengan Dokumen Kebijakan Umum Anggaran dan Prioritas Plafon Anggaran Sementara (KUA-PPAS) Kota Mataram Tahun 2015 - Dwi Anugrah Putra; Prayitno Basuki; Sri Pancawati Martiningsih (Journal of Accounting and Investment, 2017)
The purpose of this study is to analyze the effect of human resources capacity, budget planning, budgeting politics and public policy to the synchronization of APBD document and KUA-PPAS document, with the public transparency as moderating variable. The population of this study was board member and officer/staff that involved in the preparation of RKA-SKPD document. This study using purposive sampling technique, which is then analyzed by the multiple regression analysis and moderated regression analysis. Partial results of hypothesis testing showed that human resources capacity, budget planning and budgeting politic has significant positive effect, while the public policy does not affect to the synchronization of APBD document and KUA-PPAS document. The results of moderated regression analysis showed that the public transparency as moderating variable failed to moderate the relationship between human resources capacity, budget planning, budgeting politics and the public policy with the synchronization of APBD document and KUA-PPAS document. The implications of this study may provide an explanation for the basic concept of synchronization in the process of preparing documents for planning and budgeting, provide benefits in the practice of planning and budgeting, as well as provide input and consideration for Local Government, in determining policies relating to the synchronization of planning and budgeting documents.